Antimicrobial alkaloids from the leaves of Pandanus amaryllifolius - Hanna Mae C. Laluces, Atsushi Nakayama, Maribel G. Nonato, Thomas Edison dela Cruz, Mario A. Tan (Journal of Applied Pharmaceutical Science, 2015)
Chemical investigation on the crude base of the Pandanus amaryllifolius leaves led to the isolation and identification of pandamarilactone-1 (1), pandamarilactone-32 (2), pandamarilactonine-A (3), and pandamarilactonine-B (4). Their structures were elucidated based on 1H and 13C NMR and in comparison with the literature data. Compound 3 was found to be the most active among the four isolates with an MIC of 15.6 µg/mL and MBC of 31.25 µg/mL against Pseudomonas aeruginosa. This is the first report on the antimicrobial activity of the isolated alkaloids from the genus Pandanus.
Keywords: Pandanus, Pandamarilactonine, Pandamarilactone, Pandanus amaryllifolius, MIC, MBC.